Evaluation of an Emergency Department Triage Screening Tool for Suspected Severe Sepsis and Septic Shock. Issue 1 (January 2014) - Patocka, Catherine; Turner, Joel; Xue, Xiaoqing; Segal, Eli
Abstract Early identification of septic patients is important to prevent delays in appropriate management. To improve detection of septic patients presenting to the emergency department (ED), we implemented a triage screening tool. Our study sought to determine the effect of this tool on time to antibiotics in patients with suspected severe sepsis or septic shock presenting to the ED. This was a retrospective chart review examining the time interval to antibiotics pre‐ and postimplementation of the triage tool. Multiple linear regression analyses were conducted to evaluate the effect of the triage tool on time to antibiotics while controlling for the effect of level of triage. We identified 185 patients with severe sepsis or septic shock in the pretriage tool group and 170 patients in the posttriage tool group. The mean time (in minutes) to antibiotics (±SD) in the pre‐ and postcohorts was 283 (±213) and 207 (±150), respectively. The multivariable analysis showed that the mean time to antibiotics decreased by 21% (95% CI 6–36%, p < .0074) comparing pre‐ versus posttriage tool implementation. The use of a sepsis triage screening tool significantly decreased the time to antibiotics in patients presenting to the ED with suspected severe sepsis or septic shock.